Filipino Students' Perceptions on Indonesian Non-Native English-Speaking Teachers through the SEA Teacher Project - Hayfa Amanda Putri (Universitas Negeri Surabaya, 2024)
SEA Teacher Project is one of the international teaching practicums that can be participated by the students from Education majors to be globalized future educators. This study aims to find out the perceptions of Filipino students toward the Indonesian Non-Native English-Speaking Teachers (NNESTs) from Universitas Negeri Surabaya and toward the benefits of the SEA Teacher Project itself. A mixed-method analysis with an explanatory sequential research design was used to describe the experience of the total of 42 students and teachers in the presence of Indonesian Non-Native English-Speaking Teachers (NNESTs) at BISCAST Laboratory High School. The result from the questionnaire and interview data revealed that the students had good perceptions of the Indonesian Non-Native English-Speaking Teachers (NNESTs) and SEA Teacher Project from the four aspects including the attitude, the learning process, the perceived linguistic abilities, and the SEA Teacher Project. By conducting this research, the Indonesian Non-Native English-Speaking Teachers (NNESTs) from Universitas Negeri Surabaya received great exposure from the host community through the SEA Teacher Project.